2019
DOI: 10.1177/0731948719892075
|View full text |Cite
|
Sign up to set email alerts
|

The Relationships Among Temporal Processing, Rapid Naming, and Oral Reading Fluency in Chinese Children With and Without Dyslexia

Abstract: The relationships among visual and auditory temporal processing, rapid naming, and oral reading fluency in Chinese children with and without dyslexia were examined. Primary school-aged Chinese children with dyslexia ( N = 47) and chronological-age-matched controls ( N = 47) were recruited. Temporal processing, rapid naming, oral reading fluency, Chinese character reading, and nonverbal IQ were assessed. There were significant correlations among visual and auditory temporal processing, rapid naming, and oral re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 77 publications
1
1
0
1
Order By: Relevance
“…In other words, distinct patterns emerged for Chinese children with and without reading disabilities, which could be explained by the distinct cognitive profiles of the two groups of children in terms of their reading comprehension. These results echo the results of former studies that revealed that children with reading disabilities have different cognitive profiles than their peers without reading disabilities in both alphabetic languages (e.g., Reid et al., 2007) and Chinese (e.g., Chung et al., 2010; Wang, 2020; Wang et al., 2018). Such results imply the existence of heterogeneous natures and multifactorial deficits for students with reading disabilities and typically developing children with similar chronological ages or reading levels (e.g., Tobia & Marzocchi, 2014; Wang & Yang, 2018).…”
Section: Discussionsupporting
confidence: 90%
“…In other words, distinct patterns emerged for Chinese children with and without reading disabilities, which could be explained by the distinct cognitive profiles of the two groups of children in terms of their reading comprehension. These results echo the results of former studies that revealed that children with reading disabilities have different cognitive profiles than their peers without reading disabilities in both alphabetic languages (e.g., Reid et al., 2007) and Chinese (e.g., Chung et al., 2010; Wang, 2020; Wang et al., 2018). Such results imply the existence of heterogeneous natures and multifactorial deficits for students with reading disabilities and typically developing children with similar chronological ages or reading levels (e.g., Tobia & Marzocchi, 2014; Wang & Yang, 2018).…”
Section: Discussionsupporting
confidence: 90%
“…A passage reading fluency was adopted from a previous study ( Wang, 2020 ). The passage used in this task contains third-grade-level Chinese characters to reach the function of automaticity in oral reading fluency [for a review, see Fuchs et al (2001) ].…”
Section: Methodsmentioning
confidence: 99%
“…Para el aprendizaje de la lectura es necesario desarrollar las habilidades básicas como son la facilidad para la decodificación, la fluidez, el vocabulario, construcción y cohesión de oraciones (Georgiou et al, 2022); así como las habilidades lingüísticas: la comprensión auditiva y lectora, además de la expresión oral y escrita, para lo cual es necesario desarrollar la conciencia fonológica, donde se utilice una metodología multisensorial (L. C. Wang, 2020), trabajando los grupos silábicos desde los más simples a los más complejos, iniciando en conocer las letras por separado primero las vocales y luego las consonantes por su sonido (Wealer et al, 2022), la falta de habilidad para leer puede deberse a problemas socio culturales, así como a diferencias ortográficas (Holopainen et al, 2020), al escaso desarrollo de las bases para la lectura como es el desarrollo de la conciencia fonológica que está implicado en el proceso de decodificación de los grafemas en fonemas, facilitando el reconocimiento de las palabras y su relación con el significado, lo cual finalmente dará la oportunidad al lector de tener una mejor comprensión del contenido del mensaje escrito (Bar-Kochva et al, 2021).…”
Section: Introductionunclassified